Pengembangan Game BERKATA sebagai Media Interaktif Pembentukan Kata untuk Siswa Kelas II SD - Rani Setiawaty; Osi Putri Aprilia; Nita RosydaSetyawan (Universitas Swadaya Gunung Jati, 2026)
This study aims to develop an interactive learning media calledBERKATA (Belajar Riang Membentuk Kata or Learning to FormWords Joyfully) and test its feasibility and practicality in teachingbasic literacy to second-grade elementary school students. The studyuses the Research and Development (R&D) method with the ADDIEdevelopment model, which includes the stages of analysis, design,development, implementation, and formative evaluation. TheBERKATA game media was designed to help students form simplewords gradually through interactive activities that combine visual,audio, and educational game elements in accordance with thecharacteristics of Phase A literacy in the Merdeka Curriculum. Thevalidation results showed that the BERKATA game media obtained ahighly valid category from media experts with a percentage of 95.8%and material experts with a percentage of 94.4%. In addition, theresults of the teacher response showed a very practical category witha percentage of 95%, while the student response obtained an averagepercentage of 93.3% with a very practical category. Based on theseresults, it can be concluded that the BERKATA game media is veryfeasible and practical to use as interactive learning media to improvethe word formation and early reading skills of second-gradeelementary school students.